Nutritional Composition, Bioactive Compounds, and Antioxidant Activity of Fig (Ficus carica L.) Jam Varieties: A Functional Food Perspective - Manik, Md. Masuduzzaman; Quader, Md. Fahad Bin; Masum, M Abdullah Al; Iftekhar, Afra Binte; Rahman, Sk Abidur; Sarker, Md Samun; Hossain, Delower (Health Dynamics, 2025)
Background: Figs (Ficus carica L.), widely valued in Asia and the Middle East, are recognized for their rich nutritional profile and medicinal properties, including potential anti-cancer and cardiovascular benefits. Both fresh and dried figs are abundant in fiber, trace minerals, antioxidant polyphenols, proteins, sugars, organic acids, and volatile compounds. This study aimed to evaluate the quality of fig jams prepared with three different sweeteners—white sugar, brown sugar, and honey. Methods: The jams were analyzed for their nutritional composition (fat, protein, fiber, vitamin C, carbohydrates, and total solids), chemical properties (titratable acidity and pH), bioactive compounds (total phenolic, flavonoid, and anthocyanin contents), and microbial safety (total viable count, yeast, and mold counts). Results: The findings revealed that honey fig jam had the highest acidity (0.048 ± 0.001), fiber (2.38 ± 0.002%), protein (5.95 ± 0.05%), and vitamin C (8.00 ± 0.1 mg/100g) content. White sugar fig jam exhibited the lowest moisture content (36.28 ± 0.28%) and ash percentage (0.70 ± 0.05%). The total soluble solids (TSS) were highest in brown sugar fig jam (67 ± 1.00%) and slightly lower in white sugar and honey fig jams (66 ± 1.00%). Significant differences (p < 0.05) in phytochemical compounds were observed among the samples. Conclusion: These results highlight the influence of sweeteners on the quality attributes of fig jam, with brown sugar emerging as a favorable option for optimizing both nutritional value, chemical quality and sensory properties. This study provides valuable insights for the development of fig-based products, contributing to the growing demand for functional foods.